VIS-A-VIS-A-VIS 200 : Review of the exhibition catalogue Vis-a-Vis 200. Arheološka baština otoka Visa u povodu 200. obljetnice Arheološkog muzeja u Splitu (Archaeological heritage of the island of Vis on the occasion of the 200th anniversary of the Archaeol (Archaeologia Adriatica, 2022)
Archaeological heritage of the island of Vis, including, for instance, Talež hillfort, ancient Issa or Vela Svitnja shipwreck, has a special meaning for many archaeologists drawn to the islands and the seas.